A one-pot metal-free protocol for the synthesis of chalcogenated furans from 1, 4-enediones and thiols. Issue 4 (11th January 2019) - Rajeshkumar, Venkatachalam; Neelamegam, Chinnaraj; Anandan, Sambandam
Abstract : Transition-metal-free synthesis of chalcogenated furans through the sequential thiol-Michael/Paal–Knorr reaction of 1, 4-enediones in the presence of a catalytic amount of p -toluene sulfonic acid has been developed. Abstract : Transition-metal-free synthesis of chalcogenated furans through the sequential thiol-Michael/Paal–Knorr reaction of 1, 4-enediones in the presence of a catalytic amount of p -toluenesulfonic acid has been developed. The present one-pot strategy involves the thiol Michael addition to 1, 4-enediones in an anti-Markovnikov fashion with the formation of a new C–S bond, followed by intramolecular dehydrative annulation in the presence of cat . TsOH delivering fully substituted furans in good to excellent yields (50–99%). The reaction is compatible with a wide range of substrates and also capable of multi-gram scale synthesis of chalcogenated furans.